Strategic Human Resource Management Responses to Teacher Shortage in Indonesian Rural Vocational Schools - Fitriatul Maqfiroh; Anindya Prastiwi Setiawati; Nugrahini Susantinah Wisnujati (jfpublisher, 2026)
The shortage of qualified teachers in private vocational schools located in rural and remote regions of Indonesia represents a persistent structural challenge that directly undermines educational continuity and institutional sustainability. This study investigates the factors contributing to educator shortages at SMKS Al Fajar Parenggean, East Kotawaringin Regency, Central Kalimantan, and analyses the strategic human resource management responses adopted by the school in addressing these conditions. A qualitative descriptive approach with a case study design was employed, with data collected through in-depth interviews with the school principal, productive teachers, and Dapodik operators, complemented by participatory observation and documentation review. Data were analysed using the Miles, Huberman, and Saldaña interactive model, with validity established through source and theoretical triangulation. Three principal causal factors were identified: teacher migration to government institutions through ASN/PPPK recruitment, the exclusionary provisions of the Dapodik registration system, and the absence of certified Dayak language instructors following mandatory regional language policy enforcement. The school responded by implementing five integrated SHRM elements, namely adaptive leadership, community-based alumni recruitment, cross-disciplinary staffing collaboration, strategic workforce planning, and performance review, supported by social media-based digital literacy development. The findings demonstrate that locally grounded SHRM, anchored in community networks and indigenous cultural competencies, constitutes a viable and replicable adaptive governance framework for rural vocational schools confronting structural human resource constraints.